Analisis Kebutuhan Pengembangan LKPD Berbasis Problem Based Learning pada Materi Sistem Gerak Fase F SMA - Mutia Ramadina; Helendra Helendra (MASALIQ, 2025)
Indonesia’s national education system is evolving in line with the implementation of Kurikulum Merdeka, which aims to cultivate students who are faithful, morally upright, and competent, with an emphasis on student-centered learning and the strengthening of 21st-century competencies such as critical thinking. In biology, students often find it difficult to understand complex material such as the locomotor system, thereby necessitating innovative learning media, including Problem-Based Learning (PBL)-based student worksheets (Lembar Kerja Peserta Didik, LKPD). This study aims to analyze students’ needs regarding the development of PBL-based LKPD on the locomotor system topic. The research employed a Research and Development (R&D) method using the Four-D model, focusing at this stage on the define phase. The research subjects consisted of one biology teacher and 35 Grade XI students at SMAN 3 Payakumbuh. Data were analyzed descriptively and qualitatively to obtain an overall picture of the needs for instructional material development. The teacher questionnaire revealed constraints in time management and suboptimal use of LKPD, while the student questionnaire indicated that the learning media were perceived as less effective, the worksheets were visually unappealing, and the material was overly dense, thereby reducing learning motivation. The locomotor system topic was selected because it is closely related to everyday life and has the potential to foster critical thinking skills. Therefore, the development of PBL-based LKPD on the locomotor system is required to support more active learning, enhance students’ willingness to think, and make the learning process more meaningful for them.